Traditional leadership and a simpler way to accountability in local government - Matshabaphala, M. D. J. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
Service delivery, more especially the delivery of public value, has for years on end traditionally been carried out by a multiplicity of partnerships as in elected leaders, public officials, leaders from organs of civil society and traditional leaders or authority. Partnerships in the delivery of services are in the main predicated on the impulses of enhancing the quality of the people’s lives. Literature on public and development management studies alludes to the understanding that the people’s quality of life can be enhanced through making them happy, and that one of the domains of a people’s happiness is good governance that is defined by accountability. This paper focuses on the role of traditional leaders or authority in ensuring accountability and good governance in the delivery of services. Some traditional leaders or authority tend to lean towards closed systems of leadership as in practices of authoritarianism, traditionalism, centralism and other attendant closed systems approaches and styles of leadership. Such practices and behaviours tend to lead to the escalation of deficits and deficiencies on the accountability and good governance infrastructure. With the onset of the open systems and the attendant transformation of the public service landscape, a leadership style recalibration imperative is being visited on traditional authority. The open systems paradigm brings with it the knowledge society that is affirming its being and demanding accountability from those charged with the responsibility of providing leadership in the delivery of public value. This paper seeks to postulate a simpler way leadership paradigm for ensuring that traditional authority is in synchronicity with the realities of the new and evolving knowledge society. The fundamentals of traditional leadership, more especially in Africa, are found to be in resonance with the philosophies and principles of the open systems paradigm as also in the simpler way approach to leadership. The simpler way approach to leadership demands that there be more accountability from people charged with the responsibility of leadership. It demands that people or citizens be respected as human beings and meaning giving subjectivities.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Accountability; Leadership paradigm; Traditional leadership; Public value; Service delivery; Government accountability; Local government -- South Africa